Bilateral Concordance of the Fundus Hyperautofluorescent Ring in Typical Retinitis Pigmentosa Patients. (June 2015) - Sujirakul, Tharikarn; Davis, Richard; Erol, Deniz; Zhang, Lijuan; Schillizzi, Giuseppe; Royo-Dujardin, Leticia; Shen, Sherry; Tsang, Stephen
Abstract Background: It has long been assumed that in retinitis pigmentosa, disease presentation and progression are symmetrical. This study investigated whether hyperautofluorescent ring size, one known marker of disease progression, is symmetrical in typical RP patients. Materials and Methods: A total of 88 patients with typical retinitis pigmentosa were enrolled in the study. Each presented with a hyperautofluorescent ring when imaged at baseline with fundus autofluorescence (AF). Vertical and horizontal diameters were analyzed according to mode of inheritance and age group. Seven of 88 patients had data missing in one eye and were excluded from further analysis. Results: There was no significant relationship between hyperautofluorescent ring diameter and inheritance mode. There was a tendency toward smaller ring size with age and 3.7% of subjects displayed marked asymmetry in ring size between right and left eyes, although their electroretinogram results did not differ. Overall, when patients were considered as a group, there was a high correlation between right and left eyes' horizontal and vertical diameters (r = 0.99, p < 0.0001; r = 0.98, p < 0.0001). Comparing individual patients' eyes, and accounting for measurement error, a smaller majority of patients displayed symmetry of the hyperautofluorescent ring in both dimensions (85.7% in the vertical dimension, 87.3% in the horizontal dimension). Conclusion: This study confirmed the highly symmetrical nature of the hyperautofluorescent ring in RP patients, except in a small subgroup. AF results, which provide less variability per image, and are consistently interpreted between different observers, may be a more sensitive and reliable method for testing symmetry than many functional tests.